2016
DOI: 10.3103/s1063457616020052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the deposition parameters on the phase–structure state, hardness, and tribological characteristics of Mo2N/CrN vacuum–arc multilayer coatings

Abstract: Abstract-A complex study has been performed of the effect of the technological parameters, which are responsible for the energy states of deposited particles, on the elemental, phase and structure composi tions, hardness, and tribological characteristics of formed vacuum-arc multilayer Mo 2 N/CrN systems with a nanometric thickness. The formation of two phase and structure types has been defined in combined nitride layers: γ Mo 2 N/CrN with the isostructural cubic crystalline lattices and γ Mo 2 N/CrN with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The formation of the α-Mo phase can be explained by the dependence of the coat nitrogen content on nitrogen pressure. It has been shown that in coatings formed at sure 9.33 × 10 −2 Pa, the nitrogen content is nearly two times lower than in coatings duced at a higher pressure, 0.4 Pa [55].…”
Section: Phase Analysismentioning
confidence: 99%
“…The formation of the α-Mo phase can be explained by the dependence of the coat nitrogen content on nitrogen pressure. It has been shown that in coatings formed at sure 9.33 × 10 −2 Pa, the nitrogen content is nearly two times lower than in coatings duced at a higher pressure, 0.4 Pa [55].…”
Section: Phase Analysismentioning
confidence: 99%
“…Therefore, repetition of this process many times allowed obtaining multilayer TiN/ZrN coatings. The pressure of the nitrogen in a chamber (P N ), the bias voltage applied to the substrate (U b ) and the deposition time (t) were the key parameters that influenced properties and structure of the vacuum-arc coatings [121,122].…”
Section: Structure Phase Composition Mechanical and Tribological Prmentioning
confidence: 99%
“…The highest value of the adhesion strength attained in coatings of series 1 and is 179. 33 GPa, which is a high index [22].…”
Section: Resultsmentioning
confidence: 98%